THE SCIENTIFIC SIGNIFICANCE OF THE DEPENDENCE ON THE CRITICAL POINT OF DAMAGE TO GRAIN PRODUCTS DURING STORAGE CONDITIONS WITH THE “POTATO DISEASE” - Kholikov, Zukhriddin; Akhmedov, Azimjon (Innovatsion texnologiyalar, 2024)
This work, using a new instrumental method and a new indicator, provides a quantitative, objective and reliable assessment of the quality of grain and grain products when assessing their damage by pathogens “potato stick disease” along the entire technological chain of production of bread and bakery products from grain. In identifying patterns of interrelation between the enzymatic activity of spore-forming bacteria Bacillus subtilis in the manifestations of “potato disease,” the results of experimental and production studies of its microbiota in 1 g from 107 to 109 KOE/g are presented